Patterns of antimicrobial drug use in veterinary primary care and specialty practice: A 6‐year multi‐institution study - Robert Goggs; Julie M. Menard; Craig Altier; Kevin J. Cummings; Megan E. Jacob; Denise F. Lalonde‐Paul; Mark G. Papich; Keri N. Norman; Virginia R. Fajt; H. Morgan Scott; Sara D. Lawhon (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Combatting antimicrobial resistance requires a One Health approach to antimicrobial stewardship including antimicrobial drug (AMD) use evaluation. Current veterinary AMD prescribing data are limited. Objectives To quantify companion animal AMD prescribing in primary care and specialty practice across 3 academic veterinary hospitals with particular focus on third‐generation cephalosporins, fluoroquinolones, and carbapenems. Animals Dogs and cats presented to 3 academic veterinary hospitals from 2012 to 2017. Methods In this retrospective study, AMD prescribing data from 2012 to 2017 were extracted from electronic medical records at each hospital and prescriptions classified by service type: primary care, specialty practice or Emergency/Critical Care (ECC). Hospital‐level AMD prescribing data were summarized by species, service type, AMD class, and drug. Multivariable logistic full‐factorial regression models were used to estimate hospital, year, species, and service‐type effects on AMD prescribing. Estimated marginal means and confidence intervals were plotted over time. Results The probability of systemic AMD prescribing for any indication ranged between 0.15 and 0.28 and was higher for dogs than cats (P < .05) apart from 2017 at hospital 1. Animals presented to primary care were least likely to receive AMDs (dogs 0.03‐0.15, cats 0.03‐0.18). The most commonly prescribed AMD classes were aminopenicillins/β‐lactamase inhibitors (0.02‐0.15), first‐generation cephalosporins (0.00‐0.09), fluoroquinolones (0.00‐0.04), nitroimidazoles (0.01‐0.06), and tetracyclines (0.00‐0.03). Among the highest priority classes, fluoroquinolones (dogs 0.00‐0.09, cats 0.00‐0.08) and third‐generation cephalosporins (dogs 0.00‐0.04, cats 0.00‐0.05) were most frequently prescribed. Conclusions and Clinical Importance Antimicrobial drug prescribing frequencies were comparable to previous studies. Additional stewardship efforts might focus on fluoroquinolones and third‐generation cephalosporins.